Effect Of High Load Strengthening Exercise Along With Phonophoresis On Plantar Fasciitis Pain And Foot Function - Bera, Soumyabrata; Tiwari, Mukesh; Gangopadhaya, Suparna; Saharan, Ajeet (Journal of Neonatal Surgery, 2025)
Background: Plantar fasciitis (PF) is one of the most common causes of heel pain in adults, often resulting from repetitive mechanical loading of the plantar fascia. In India, the prevalence of PF is high among individuals involved in prolonged standing, overweight populations, and those wearing improper footwear. Although exercise therapy and physical modalities such as ultrasound or phonophoresis are widely used, the combined effect of high-load strengthening exercises and phonophoresis has not been extensively studied in Indian settings. Objective: To evaluate the effectiveness of high-load strengthening exercise along with phonophoresis on pain and foot function among patients with plantar fasciitis. Methods: A single-arm pre–post experimental study was conducted at the Department of NCD Physiotherapy OPD, Kharagpur Sub-Divisional Hospital, West Bengal. Thirty participants (20 female, 10 male; mean age 41.27 ± 9.88 years) with chronic plantar fasciitis were included. Participants underwent a 4-week program of high-load strengthening of the calf and plantar fascia using progressive heel raises with a rolled towel under the toes to activate the Windlass mechanism, combined with dexamethasone (0.5%) phonophoresis applied thrice weekly. Pain intensity and foot function were assessed using the Numeric Pain Rating Scale (NPRS) and Foot Function Index (FFI) before and after the intervention. Data were analysed using paired t-tests (p < 0.05). Results: Significant improvements were observed in both outcomes. Mean NPRS reduced from 5.4 ± 1.4 to 2.43 ± 1.61 (p < 0.0001), while FFI decreased from 43.29 ± 11.72 to 18.41 ± 12.0 (p < 0.0001). Participants reported a 55% reduction in pain and 57% improvement in function, with no adverse events. Conclusion: The combination of high-load strengthening and phonophoresis significantly improved pain and foot function in plantar fasciitis within four weeks. This integrated approach is safe, cost-effective, and feasible in Indian physiotherapy settings, addressing both mechanical and inflammatory components of the condition